Role of Exosomal miRNAs in Heart Failure - Xue, Ruicong; Tan, Weiping; Wu, Yuzhong; Dong, Bin; Xie, Zengshuo; Huang, Peisen; He, Jiangui; Dong, Yugang; Liu, Chen (Frontiers in Cardiovascular Medicine, 2020)
Heart failure is the terminal outcome of majority of cardiovascular diseases that lack specific diagnostic biomarkers and therapeutic target. It contributed to most of cardiovascular hospitalization and death despite of the current therapy. Therefore, it is desperate to explore potential molecules improving the diagnosis and treatment of heart failure. MicroRNAs are non-coding small RNAs that have been proved the regulate heart failure. Recently, the subcellular distribution analysis of miRNAs is calling for attention since miRNAs in exosomes are discovered. Growing evidence demonstrated that exosomal miRNAs might be a promising diagnostic and therapeutic molecule for heart failure. This review summarized the role of exosomal miRNAs in heart failure in the prospect of molecular and clinical researches.